Prevalence of MRSA colonization in Japanese neonatal care unit patients in 2011. Issue 2 (28th January 2014) - Morioka, Ichiro; Takahashi, Naoto; Kitajima, Hiroyuki
Abstract Background The neonatal intensive care unit (NICU) is a high‐risk setting for transmission of methicillin‐resistant Staphylococcus aureus (MRSA). The recent prevalence of colonization with MRSA in patients and its control measures are unknown in Japanese NICU. We investigated the prevalence of MRSA colonization in patients and measures to control and prevent health‐care‐associated transmission in Japanese NICU in 2011. Methods A nationwide survey was performed in facilities certified as training hospitals for neonatologists. Data in NICU and growing care units (GCU) were collected and analyzed regarding surveillance cultures for MRSA and the proportion of MRSA‐colonized patients in September 2011. Trends in the proportion of MRSA‐colonized patients and the measures to control and prevent health‐care‐associated MRSA transmission were investigated in the surveyed NICU in 2000, 2003, and 2011. Results A total of 168 NICU and 158 GCU were analyzed. The proportions of NICU and GCU that conducted regular surveillance cultures for MRSA were 81% and 66%, respectively. MRSA colonization was not found in 53% of NICU and in 45% of GCU. The percentage of NICU reported to be free of MRSA colonization increased over time. Use of alcohol‐based hand rub and gloves by clinical staff and cohorting for identified MRSA‐positive patients became more common in 2011 than in 2000 or 2003. Conclusions Approximately half of Japanese NICU did not observe any patients with MRSA colonization in September 2011. Control and prevention measures have changed to use of alcohol‐based hand rub and gloves in the last decade.